Management of a large radicular cyst: A non-surgical endodontic approach - Shweta Dwivedi; Chandra Dhar Dwivedi; Thakur Prasad Chaturvedi; Harakh Chandra Baranwal (Wolters Kluwer Medknow Publications, 2014)
A radicular cyst arises from epithelial remnants stimulated to proliferate by an inflammatory process originating from pulpal necrosis of a non-vital tooth. Radiographically, the classical description of the lesion is a round or oval, well-circumscribed radiolucent image involving the apex of the tooth. A radicular cyst is usually sterile unless it is secondarily infected. This paper presents a case report of conservative non-surgical management of a radicular cyst associated with permanent maxillary right central incisor, right lateral incisor and right canine in a 24-year-old female patient. Root canal treatment was done together with cystic aspiration of the lesion. The lesion was periodically followed up and significant bone formation was seen at the periapical region of affected teeth and at the palate at about 9 months. Thus, nonsurgical healing of a large radicular cyst with palatal swelling provided favorable clinical and radiographic response.